Algumas aplicações da parametrização de Gauss - Albuquerque, Ivan Araújo Cordeiro de (1988)
In the study of hypersurfaces in Riemannian varieties the concept of stiffness plays an important role, namely to classify hypersurfaces less than rigid movements of the ambient space. Our work is divided into three parts. In the first one we fix the notations and describe some basic concepts necessary to the general understanding of the work. In the second part, we find the construction of the Gauss parametrization and we show that a hypersurface has Gauss parameterization, if, if only, it has constant relative nullity. In the third and last we study the theorems of stiffness and among these are the main result mentioned above.